Arithmetic Abilities in Children With Developmental Dyslexia: Performance on French ZAREKI-R Test. - De Clercq-Quaegebeur, Maryse; Casalis, Séverine; Vilette, Bruno; Lemaitre, Marie-Pierre; Vallée, Louis (Journal of Learning Disabilities)
A high comorbidity between reading and arithmetic disabilities has already been reported. The present study aims at identifying more precisely patterns of arithmetic performance in children with developmental dyslexia, defined with severe and specific criteria. By means of a standardized test of achievement in mathematics (Calculation and Number Processing Assessment Battery for Children; von Aster & Dellatolas, 2006), we analyzed the arithmetic abilities of 47 French children with dyslexia attending 3rd, 4th, and 5th grade. Of them, 40% displayed arithmetic deficits, mostly with regard to number transcoding and mental calculation. Their individual profiles of performance accounted for varying strengths and weaknesses in arithmetic abilities. Our findings showed the pathway for the development of arithmetic abilities in children with dyslexia is not unique. Our study contrasts with the hypotheses suggesting the mutual exclusiveness of the phonological representation deficit and the core number module deficit.